INTERNALIZATION OF ANTI-RADICALISM VALUES IN LEARNING AT DAYAH CITY OF SABANG - Munawar; Hasan Basri; Mawardi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
Radicalism is one of the challenges that can threaten national unity and give rise to a narrow and exclusive understanding of religion. Islamic educational institutions, including Dayah (traditional Islamic boarding schools), hold a strategic role in shaping santri (students) with moderate, tolerant, and nationally-minded character through the internalization of anti-radicalism values. This study aims to analyze the process of internalizing anti-radicalism values in learning at Dayah in Sabang City, to identify the strategies applied by teachers ( teungku ), and to examine the supporting and inhibiting factors in their implementation. The research employed a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation studies involving Dayah leaders, teachers, and santri at Dayah Darul Wa'di Istiqamatuddin and Dayah Darul Hijrah, Sabang City. Data were analyzed through data reduction, data display, and conclusion drawing, with triangulation applied to ensure validity. The findings show that the internalization of anti-radicalism values is carried out in an integrated manner through the cultivation of wasathiyah (religious moderation), tasamuh (tolerance), tawazun (balance), i'tidal (firmness/non-violence), ukhuwah Islamiyah (Islamic brotherhood), love for the homeland, and the study of classical texts that Islam as rahmatan lil -' alamin . The internalization process occurs through three interrelated stages: value transformation (the transmission of religious knowledge), value transaction (dialogical interaction between teachers and students ), and trans-internalization (exemplary conduct and habituation within twenty-four-hour dayah life). Supporting factors include the commitment of dayah leadership, teacher competence and exemplary behavior , an integrated curriculum, and a conducive educational environment, while obstacles arise from the influence of digital media, unverified religious information, limited teaching materials, and restricted programs for strengthening religious moderation. The study concludes that the internalization of anti-radicalism values in the Dayah of Sabang City has continued regularly and has contributed to shaping santri who are moderate, tolerant, and strongly committed to national values.